Deformed Quantum Energy Spectra with Mixed Harmonic Potential for Nonrelativistic Schrödinger Equation - Abdelmadjid Maireche (Журнал нано- та електронної фізики)
The paper describes the deformed Hamiltonian for Schrödinger equation with mixed harmonic potential known by sextic potential and the corresponding spectrum of energies which depended with 3-new quantum numbers (j = l ± 1/2, l) and s = 1/2 in the non-commutativity infinitesimal parameter θ.